Developing a role for patients and the public in the implementation of health and social care research evidence into practice: the PIPER study (Pathways to Implementation for Public Engagement in Research) realist evaluation protocol - Sophie Staniszewska; Julia Walsh; Joe Langley; Krysia Dziedzic; Alice Moult; Nick Andrews; Chris Bain; Lindsay Bearne; Paul Bird; Tracy Gazeley; Richard Grant; Gary Hickey; et al. (Research Involvement and Engagement)
Abstract Background While patients and the public are routinely involved as active collaborators in health and social care research, they are rarely involved in the implementation of research. The PIPER (Pathways to Implementation for Public Engagement in Research) research questions are: 1. How can patients, carers, service users and the public be involved in the implementation of health and social care research evidence into practice? 2. What types of roles, contributions and impact can patients, carers, service users and the public make to the implementation of health and social care evidence into practice? 3. How can we support patients, service users, carers and the public to contribute to the implementation of health and social care evidence into practice? 4. How can we co-produce the knowledge that explores a greater role for patients, carers, service users and the public in the implementation of health and social care evidence into practice? Methods Our overarching methodological framework is realist evaluation. This study includes four work packages with a cross-cutting co-production theme. •Work Package 1: A realist review of published literature, grey literature and sources such as blogs. •Work Package 2: Interviews with 40–60 people using a realist approach. •Work Package 3: A series of workshops to co-design the PIPER Toolkit. •Work Package 4: Pilot evaluation of the PIPER Toolkit. Results The scoping of the literature will be informed by the development of an initial programme theory that identifies the potential breadth of the field of public involvement in implementation. Data from the WP2 interviews will be used to iteratively refine the development of the context, mechanism and outcomes (CMOs). This will inform the PIPER Toolkit, which will consist of a set of ‘Guiding Principles’ supported by ‘Practical Resources.’ The PIPER Toolkit will enable an individual or a group to plan and undertake implementation activities. More specifically, the Guiding Principles will enable the Practical Resources to be tailored to specific implementation strategies for an individual or group. Discussion Patient and public involvement in implementation is an emerging area of practice and is likely to significantly strengthen over the next decade. The PIPER Toolkit will recognise this early stage of development, identifying the key system enablers that organisations need to have in place to support this activity. The Toolkit will support patients and the public and implementation teams to navigate the field of implementation practice. The PIPER study will challenge the field of implementation and knowledge mobilisation research to develop clearer forms of partnership with patients and the public in both research and practice.